Pengenalan Media Pembelajaran Jaring-Jaring Kubus Berbasis 3D Pada Materi Bangun Ruang Kubus Di SDN Aman Damai - Reflina Reflina; Yasmin Salsabila; Vania Retna Syahrani; Zamaiyah Zamaiyah; Sri Rezeki; Putri Nabila Lubis (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Mathematics learning activities in elementary schools are generally still monotonous and the lack of use of learning media in helping teachers convey lesson material. The purpose of community service activities is to introduce 3D based learning media to students of SDN Aman Damai about Cube Building  which include nets, and elements of cube building. The method used in community service activities is the Service Learning method. The results of the implementation of community service activities are an increase in students' understanding of cube building material and students' enthusiasm in learning mathematics. The conclusion of community service activities is that 3D based learning media helps teachers to visualize the shape of the cube physically or real.